2017
DOI: 10.1177/1687814017723294
|View full text |Cite
|
Sign up to set email alerts
|

Spacing and geometric design indexes of auxiliary lanes on two-lane highway in China

Abstract: Auxiliary lanes on two-lane highway are lanes setting on the right side of highway for the slow vehicles, and they can provide safe overtaking chances for cars using the original lane instead of the opposite lane. Based on the principle that the net benefit is greater than zero, the calculation model of the minimum spacing of auxiliary lanes on two-lane highway is established. After calibrating the model parameters, recommended minimum spacing values for auxiliary lanes are given corresponding to different hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Similarly, lane position and speed have varying degrees of influence on the lateral oscillation on straight sections of freeways [28]. It has been shown that the lane width is composed of lateral oscillation, vehicle width, and outside clearance [33]. However, Cheng's study only used 70 questionnaires to determine the lateral offset at different speeds, which may lack powerful data support.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lane position and speed have varying degrees of influence on the lateral oscillation on straight sections of freeways [28]. It has been shown that the lane width is composed of lateral oscillation, vehicle width, and outside clearance [33]. However, Cheng's study only used 70 questionnaires to determine the lateral offset at different speeds, which may lack powerful data support.…”
Section: Discussionmentioning
confidence: 99%
“…satisfying the similarity conditions specified by the third theorem as much as possible, the main factors that play a role should be grasped, minor factors should be omitted, and the primary similarity conditions should be maintained to obtain an approximate similarity that is sufficiently accurate in practice. The main mechanical parameters of the model following the above similarity relationship are set as follows [21][22][23][24]:…”
Section: Selection Of Similar Materials For the Model 421 Model Test ...mentioning
confidence: 99%
“…imate similarity that is sufficiently accurate in practice. The main mechanical parameters of the model following the above similarity relationship are set as follows [21][22][23][24]:…”
Section: Selection and Preparation Of Materials For Surrounding Rock ...mentioning
confidence: 99%
“…Kirby et al [21] prepared an evaluation process to assess the benefit-cost ratio of implementing 2 + 1 highways depending on terrain type, traffic volume (AADT), percentage of heavy vehicles, and length and spacing of passing lanes. Recently, Cheng et al [52] developed another framework to perform cost-benefit analyses of providing auxiliary passing lanes on two-lane highways based on traffic simulations and questionnaires. Benefits included the reduction of crash-related costs and saved time per kilometer, while costs included construction and maintenance.…”
Section: Median Barriersmentioning
confidence: 99%